ANALISIS KETERSEDIAAN TAMAN KOTA KETERKAITANNYA DENGAN TATA RUANG KOTA JAYAPURA - Hosana Gracia Laimeheriwa; Yundy Hafizrianda; Herbert Innah (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2021)
Papua Province is one of the provinces in Indonesia which is currently experiencing rapid infrastructure development. The capital of Papua Province is Jayapura City, where currently Jayapura City is one of the cities that is developing the provision of green open space (RTH) in the form of a City Park. The availability of City Parks in Jayapura City is in fact empirically the use or interest of the community towards city parks is lacking. This is what encourages the author to examine how the distribution of City Parks to Jayapura City Spatial Planning. The purpose of this study was to describe the condition of RTH in the form of City Parks in Jayapura City, to find out the distribution of City Parks in Jayapura City and to analyze the needs of City Parks in Jayapura City. The method used is descriptive quantitative which aims to describe the need for green open space (City Park) in Jayapura City through the calculation of a simple mathematical formula. The results of the analysis will be the basis for the study in determining the area needed to provide green open space at the research location by comparing the available green open space. The results obtained are that there are 5 (five) city parks in North Jayapura District, Jayapura City that are inadequate, the availability of RTH for city parks is 282,000 ha and to achieve the standard requirements for the ideal area of green open space in the city, Jayapura City must fulfill 280,795 ha.